Online Based Memorandum of Understanding (MOU) Data Exchange System Design with EDI Method - Inge Virdyna; Samidi Samidi (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2021)
During the Covid 19 pandemic, every individual is required to be more creative in carrying out every activity and not make a distance as the reason an activity cannot be carried out. Documentation data, which is usually sent manually by post, will experience difficulties at this time. This research will discuss other ways that can be done to ensure the data exchange process of the Memorandum of Understanding (MOU) between PT. Bank XYZ with partners. The solution that can be implemented is to use the Electronic Data Interchange (EDI) method. EDI is an online-based data exchange method. In other words, the method of exchanging data via postal service is not necessary. Based on this research, the EDI method can meet users' needs in terms of exchanging or sending documentary data on the MOU between PT. Bank XYZ with partners. The method used in building this system design is analyzing the running system and designing the system with UML tools. The final result of the validation test of the system design through the FGD method states that the e-approval system application design of the MOU is by the specifications of the functional requirements required by the user.